ADVANTAGES AND DISADVANTAGES OF ALTERNATIVE ASSESSMENT - Shoira Kutbiddinova (FAN, TA'LIM VA AMALIYOT INTEGRATSIYASI, 2021)
The given article reviews the advantages and disadvantages of alternative assessment. Student’s assessment in schools and classrooms have always been a topic of speculation. Educators are continually working towards building an excellent assessment method that considers all the skills of a student and also recognizes their capabilities and potential. The traditional or conventional approach of assessments may not benefit the students in the best way, so a new method has emerged known as alternative or authentic assessments. This method is more inclusive and practical in its approach and has yielded some excellent results.